Youth athlete development models: A narrative review - Varghese, M.; Ruparell, S.; LaBella, C. (Sports Health: A Multidisciplinary Approach, 2022)
Context: Physical activity has shown to be beneficial for the overall physical and mental health of youth. There has been an increasing focus on youth sports moving from a recreational activity to becoming a launching pad for participation at elite levels. Several models of athlete development have emerged to guide specialized and nonspecialized athletes at an age-appropriate level, taking into consideration their physical and mental development. The purpose of this review is to summarize the current evidence and theoretical models regarding youth athlete development and discuss broader initiatives for sports participation and future directions for the field. Evidence Acquisition: An electronic databases search, including PubMed, Google Scholar, ScienceDirect, National Institutes of Health, UpToDate, and Springer was conducted. Articles from 1993 to 2021 were included. The search terms long term athlete development, LTAD model, youth physical development, youth athlete development, sports specialization, and pediatric athlete, among others, were used. Study Design: Narrative review. Level of Evidence: Levels 4 and 5. Results: Several models of youth athlete development are discussed in this article. More recent models have built on previous models to incorporate more age- and development-specific recommendations; however, no singular model could be identified as the gold standard for youth athlete development, especially given the lack of empirical data to support these models. Conclusion: Youth athlete development currently consists of several theoretical models, each with their own strengths and weaknesses, that can guide the training of young athletes to maximize their performance. Those involved in this process—physicians, athletic trainers, coaches, physical educators, and parents—should understand these various models and trial their various features to see what works best for their individual athlete with consideration given to factors such as their stage of development. Ultimately, more empirical data are required to definitively state which is the optimal approach.